2021
DOI: 10.1186/s13287-020-02061-3
|View full text |Cite
|
Sign up to set email alerts
|

Combination of lyophilized adipose-derived stem cell concentrated conditioned medium and polysaccharide hydrogel in the inhibition of hypertrophic scarring

Abstract: Background Mesenchymal stem cell-based acellular therapies have been widely exploited in managing hypertrophic scars. However, low maintenance dose and transitory therapeutic effects during topical medication remain a thorny issue. Herein, this study aimed to optimize the curative effect of adipose-derived stem cell conditioned medium (ADSC-CM) in the prevention of hypertrophic scarring. Methods In the present study, ADSC-CM was concentrated via th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…In recent years, the therapeutic application of bone marrow-derived mesenchymal stromal/stem cells (MSCs) shifted from cellular transplantation to acellular therapy, in light of a novel mechanism of action, based on the favorable effects of factors secreted by these cells. Previous work, including our own, supports the use of MSC conditioned medium (CM) for skin wound healing, on account of its stimulative properties on several key biological processes such as proliferation, migration, and angiogenesis [4][5][6][7][8][9]. Besides growth factors and cytokines, the CM (the secretome) also includes the ubiquitous large family of extracellular vesicles (EVs) comprising exosomes, microvesicles (microparticles), and apoptotic bodies.…”
Section: Introductionmentioning
confidence: 83%
“…In recent years, the therapeutic application of bone marrow-derived mesenchymal stromal/stem cells (MSCs) shifted from cellular transplantation to acellular therapy, in light of a novel mechanism of action, based on the favorable effects of factors secreted by these cells. Previous work, including our own, supports the use of MSC conditioned medium (CM) for skin wound healing, on account of its stimulative properties on several key biological processes such as proliferation, migration, and angiogenesis [4][5][6][7][8][9]. Besides growth factors and cytokines, the CM (the secretome) also includes the ubiquitous large family of extracellular vesicles (EVs) comprising exosomes, microvesicles (microparticles), and apoptotic bodies.…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, stem cells have been shown to improve tissue repair by secreting interleukins such as interleukin 6, interleukin 8, interleukin 10 and other proteins that are suitable for inducing tissue regeneration [ 21 , 22 ]. Recent studies have shown that adipose-derived stem cells are able to inhibit mRNA expression levels of COL1A1, transforming growth factor β1, connective tissue growth factor and alpha actin 2 (ACTA2) in renal fibrosis tissues, thereby playing a therapeutic role in renal fibrosis [ 23 ]. Whether or not dental pulp stem cells can play a role in the repair of skin scars by inhibiting the proliferation and migration of keloid fibroblasts through the secretion of cytokines has not been clearly reported thus far.…”
Section: Discussionmentioning
confidence: 99%
“…In the experimental model of ischemia, the retention time of MSC-EXOs with an injectable hydrogel was prolonged, which enhanced the therapeutic effect of exosomes ( 127 ). In the experiment of preventing hyperplastic scar in rabbit ear model, adipose-derived stem cell conditioned Medium (ADSC-CM) was combined with polysaccharide hydrogel to prolong the therapeutic effect of cytokines ( 128 ). Third, in order to ensure the safety of patients treated with MSC-EXOs, the route and dose of exosomes must be explored.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%